Factors associated with patient and health system delays in diagnosis and treatment of tuberculosis in Montenegro, 2015–2016 - Bojovic, Olivera; Medenica, Milic; Zivkovic, Danko; Rakocevic, Bozidarka; Trajkovic, Goran; Kisic-Tepavcevic, Darija; Grgurevic, Anita (PLOS ONE, 2018)
Background Fundamental measures of control of tuberculosis are early detection and timely treatment of the affected. The aim of this study was to identify factors associated with patient-related and health system-related delays among patients with tuberculosis in the Republic of Montenegro. Methods A cross-sectional study included 130 tuberculosis patients older than 15 years of age. The inclusion criteria were diagnosis of tuberculosis based on clinical, pathohistological and microbiological findings. Patient delay referred to the number of days between the onset of symptoms and the first consultation with general practitioner (GP). Health system delay represented the number of days between the first consultation with GP and the initiation of tuberculosis treatment.We classified delays longer than median delay length as 'prolonged delays'. Delays greater than 75th percentile of the maximum length of delay were classified as 'extreme delays'. Results Distribution of patient and health system delay in the overall delay was apprioximately equal (49% vs. 51%). Being married (OR = 2.54, p = 0.026) and having more negative attitudes towards tuberculosis (OR = 4.00, p = 0.045) were associated with extreme patient delay. Greater knowledge on tuberculosis was associated with lower likelihood of prolonged (OR = 0.24, p = 0.031) and extreme (OR = 0.30, p = 0.012) patient delay. Persons with negative sputum smear were more likely to experience prolonged (OR = 7.01, p<0.001) and extreme (OR = 4.40, p = 0.032) health system delay. Persons older than 47 years of age were more likely to experience prolonged health system delay (OR = 2.61, p = 0.042). Specialist consultation delay was associated with prolonged (OR = 1.08, p = 0.001) and extreme (OR = 1.05, p<0.001) health system delay. Conclusion Contribution to overall delay is equally distributed between the patients and the health care system. Improvement of knowledge in the general population and continuing medical education of the health care workers on tuberculosis could lead to reduction in patient and health system delays in treatment of tuberculosis.